Autophagy is essential for the maintenance of amino acids and ATP levels during acute amino acid starvation in MDAMB231 cells. (5th February 2018) - Thomas, Mark; Davis, Tanja; Loos, Ben; Sishi, Balindiwe; Huisamen, Barbara; Strijdom, Hans; Engelbrecht, Anna‐Mart
Abstract : Autophagy plays a major role in the adaptive metabolic response of cancer cells during adverse conditions such as nutrient deprivation. However, specific data that assess metabolite profiles in context with adenosine triphosphate (ATP) availability and cell death susceptibility remain limited. Human breast cancer cells, MDAMB231, and normal breast epithelial cells, MCF12A, were subjected to short‐term amino acid starvation and the cellular apoptotic and autophagic responses assessed. The role of autophagy in the control of cellular amino acid, ATP, free fatty acid, and glucose levels during amino acid starvation were compared. We demonstrate that breast cancer cells have an increased metabolic demand contributing to significant amino acid and ATP depletion in a nutrient‐poor environment. Upregulation of autophagy was important for the generation of amino acids and free fatty acids and maintenance of cellular ATP levels. In contrast to normal cells, breast cancer cells were unable to maintain the response after 12 hours of amino acid starvation. Regulation of autophagic activity in these environments had indirect consequences on cell death susceptibility. Overall, our data provide support for autophagy as an important survival mechanism capable of providing metabolic substrates when cancer cells are faced with nutrient‐deprived environments. Significance of study: The results obtained in this study helps to expand our current knowledge on how cells respond to environmental changes; the biochemical and metabolic consequences and the physiological processes activated in response. The environmental stress applied in this study is relevant to tumour physiology, and results can be translated to cancer therapeutic and clinical research areas, ultimately assisting in the specific targeting of cancer cells while avoiding harm to normal cells.